The peculiarities of a mythological worldview in Artemis Fowl series by E. Colfer - Кураш, Наталія-Марія Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article aims at studying the way of functioning of a mythological worldview in a piece of writing, using a series of novels about Artemis Fowl by Eoin Colfer as an example. The methods and techniques of the neo-mythologization conception employed by the author emphasize contemporary orientation of this work and reflect the processes of the XXI century. The mythological worldview used in a series of works about Artemis Fowl, at plot-forming, imaginative and mythopoetic levels creates a canvas, which helps the author to develop ideas of culture and education, globalization and ecology.